Pengaruh Kepemimpinan, Asuransi dan Lingkungan Fisik Terhadap Kinerja Karyawan PT. Candi Mekar (Studi Kasus Pada Karyawan Bagian Produksi PT. Candi Mekar Pemalang) - A, Angga Setyawan; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
In today's age development of competition in the business world requires each company to further optimizing and empowerment of all enterprises to better perform the optimization and empowering all its resources for the sake of survival of the company.. Human resource capacity mixed performance , as the company is moving towards efektitifas and efficiency should be able to optimize the performance of its human resources .Candi Mekar Inc. Pemalang is a company that is currently experiencing problems in their employees' performance is marked by the level of attendance from year to year is getting decrease. The decrease of the attenndance is caused by several factors such as leadership , insurance and physical environments that exist in the company .The purpose of this study was to determine the effect of leadership, insurance and physical environment on the performance of employees of Candi Mekar Inc. on the production department. This type of research is explanatory research. The population in the study were all employees of the production department and the number of samples is 100 respondents. Sampling retrieval using random sampling technique. The scale of measurement using a Rating scale. The analytical method used is the correlation test, determination, simple linear regression, multiple linear regression, t test and F test with SPSS version 18.Based on the survey result revealed that the partially leadership give positive influence on employee performance indicated by the value t count > t table ( 7.858 > 1.9845), insurance give positive affect on the employee performance indicated by the value of t count > t table (3.723 > 1.9845), and the physical environment also provides positive influence on the performance indicated by the value of t count > t table (5.515 >1.9845). in the multiple test variables leadership, insurance and physical environment give affect to the employee performance indicated by F count > F table (25.612 > 2.699). The advice can be given that the leadership needs to be an increase in terms of motivation to employees so that employee performance can be maintained , the insurance company needs to revisit the provisions of insurance policies are given so that employees feel satisfied and then the performance of employees will be increased , then the physical environment noise and air cleanliness need to be considered by the company and the company should be able to minimize the impact that can be generated by these two things by providing appropriate equipment with safety standards .